2019
DOI: 10.3390/nu11030546
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Diabetic Retinopathy through Protection against Retinal Apoptosis in Spontaneously Diabetic Torii Rats Mediated by Ethanol Extract of Osteomeles schwerinae C.K. Schneid

Abstract: Retinal apoptosis plays a critical role in the progression of diabetic retinopathy (DR), a common diabetic complication. Currently, the tight control of blood glucose levels is the standard approach to prevent or delay the progression of DR. However, prevalence of DR among diabetic patients remains high. Focusing on natural nutrients or herbal medicines that can prevent or delay the onset of diabetic complications, we administered an ethanol extract of the aerial portion of Osteomeles schwerinae (OSSCE), a Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Its low solubility, short half-life, low renal concentration, and minimal bioavailability hamper Apigenin uses. 12 Therefore, in laboratory animals, this research aimed to examine the attenuating effects of Apigenin-solid lipid nanoparticles(SLNPs) in diabetic nephropathy caused by streptozotocin (STZ) nicotinamide.…”
Section: Introductionmentioning
confidence: 99%
“…Its low solubility, short half-life, low renal concentration, and minimal bioavailability hamper Apigenin uses. 12 Therefore, in laboratory animals, this research aimed to examine the attenuating effects of Apigenin-solid lipid nanoparticles(SLNPs) in diabetic nephropathy caused by streptozotocin (STZ) nicotinamide.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18]. It was shown that quercetin has a dose-dependent effect in inhibiting proliferation of rhesus macaque choroid-retinal endothelial cells [19] and reducing apoptosis of retinal ganglion cell layer and whole retinal vessels in diabetic rats [20,21]. Meanwhile, the previous study has confirmed that quercetin could significantly inhibit the expression of retinal VEGF in diabetic rats [22].…”
Section: Discussionmentioning
confidence: 93%
“…Herbal extracts and natural compounds have traditionally been used to treat diabetes and diabetic complications [8,12,16,17]. Here, an OSSC extract and its maker compounds were tested for their inhibitory effects on apoptosis and its related mechanisms under toxic diabetic conditions in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the purities of maker compounds of OSSC extract were analyzed by HPLC [12]. Here, we evaluated whether the extract and its maker compounds could affect cell viability in MG-treated ARPE-19 cells.…”
Section: Effects Of the Ossc Extract And Its Major Compounds On The Vmentioning
confidence: 99%
See 1 more Smart Citation